2020
DOI: 10.1186/s12944-020-01393-6
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride-glucose index is associated with the severity of hepatic steatosis and the presence of liver fibrosis in non-alcoholic fatty liver disease: a cross-sectional study in Chinese adults

Abstract: Background The triglyceride-glucose index (TyG) is a reliable predictor of non-alcoholic fatty liver disease (NAFLD). Its association with the severity of hepatic steatosis and liver fibrosis in NAFLD is poorly understood. This study evaluated the relationship between these factors in NAFLD. Methods A total of 4784 participants who underwent ultrasonography were enrolled. Anthropometric and biochemical measurements were assessed. Participants with NAFLD were diagnosed by ultrasound. The degree of hepatic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 32 publications
(38 reference statements)
4
53
2
Order By: Relevance
“…As expected, several anthropometric or metabolic indices such as skeletal muscle mass [16], atherogenic index [17,18], Body Mass Index (BMI) [19], the ratio of Triglyceride (TG) to High-Density Lipoprotein cholesterol [20], visceral adipose tissue [21], Total cholesterol (TC) to High-Density Lipoprotein cholesterol ratio [22] and Triglyceride Glucose (TyG) [23,24], as well as blood pressure [25] had been reported to be associated with FL in both cross-sectional and cohort studies. However, most existing studies mainly focused on only one or two indices, which might have limitations for predicting FL considering the high complexity of the pathogenesis of FL.…”
Section: Introductionsupporting
confidence: 63%
“…As expected, several anthropometric or metabolic indices such as skeletal muscle mass [16], atherogenic index [17,18], Body Mass Index (BMI) [19], the ratio of Triglyceride (TG) to High-Density Lipoprotein cholesterol [20], visceral adipose tissue [21], Total cholesterol (TC) to High-Density Lipoprotein cholesterol ratio [22] and Triglyceride Glucose (TyG) [23,24], as well as blood pressure [25] had been reported to be associated with FL in both cross-sectional and cohort studies. However, most existing studies mainly focused on only one or two indices, which might have limitations for predicting FL considering the high complexity of the pathogenesis of FL.…”
Section: Introductionsupporting
confidence: 63%
“…Bellan et al [ 51 ] suggested that, independent of the etiology of chronic liver disease, liver fibrosis is a stronger determinant of prolonged QTc interval than fatty liver. In addition, TyG index was positively related to the presence of liver fibrosis and the severity of hepatic steatosis in NAFLD [ 52 ]. Hence, it is reasonable to suggest that TyG index may be associated with hypertension, obesity, WBC count, and liver function, thereby contributing to QTc interval prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies explored the relationship between the TyG index and NAFLD risk, these studies focused on the general population [15,18,19]. Our present study focused on the associations of the TyG index, glycemic parameters, and lipid parameters with NAFLD in a T2DM population.…”
Section: Discussionmentioning
confidence: 99%
“…Lipotoxicity and glucotoxicity, which begin in hepatocyte exposure to high lipid and glucose levels, respectively, play vital roles in the development and subsequent progression of NAFLD [14]. Thus, the TyG index has been recommended as a simple and reliable indicator to identify individuals at risk for NAFLD [15].…”
Section: Introductionmentioning
confidence: 99%